The Role of Relatives' Cognitive and Emotional Appraisals as Predictors and Mediators of Expressed Emotion: Results from the Sant Pere Claver-early Psychosis Program (SPC-EPP) in Barcelona (Spain) - Domínguez-Mártínez, Tecelli; Medina-Pradas, Cristina; Hinojosa-Marques, Lidia; Kwapil, Thomas R; Barrantes-Vidal, Neus (Early Intervention in Psychiatry, 2020)
The factors accounting for Expressed Emotion (EE) in relatives of early psychosis persons, their association with symptoms and functioning and what elements mediate between relatives’ EE and patients’ dysfunction are still not well understood. This study examined the association of relatives’ EE, attributions, distress, attachment style and perceived loss in 140 relatives of early psychosis patients attending the Sant Pere Claver-Early Psychosis Program of Barcelona. This program is an integrated need-adapted treatment that includes family-psychotherapy and psychoeducation. Results showed that EE was highly associated with relatives’ illness attributions, distress, perceived loss and attachment anxiety, and with a wide variety of early psychosis patients’ symptoms and functioning. Relatives’ distress, negative emotions about psychosis and attributions of control/blame toward the patient predicted EE. Relatives’ attachment anxiety was found to mediate the association between perceived loss and EE, while relatives’ attributions of blaming patients for their symptoms were found to mediate the relationship between EE and patients’ symptoms. Findings highlight the importance of family emotional environment in the early stages of psychosis and the need of design specific goals of intervention to improve the efficacy of treatments and prevent chronic disorders. Given that early psychosis is a critical period where relatives’ appraisals/attitudes are forming, it is fundamental that early family interventions provide proper information and specific psychological support to help relatives to: improve their understanding of the circumstances; handle difficult thoughts and emotions over the psychotic processes; reduce negative appraisals; change attributions that blame the patient; and prevent the entrenchment of high-EE attitudes.
Keywords: relatives' cognitive; emotional appraisals; expressed emotion; WOS(2)